2021
DOI: 10.15392/bjrs.v9i1a.1449
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Mango Seedlings of the Cultivar “Tommy” by Grafts Irradiated

Abstract: Due to difficulties of vegetative propagating of any pants, many tests were performed with ionizing radiation aiming the modification of the characteristics of the plants for obtaining of the improved genotypes and of smaller size. Rootstock “Espada” cultivar, were used to obtain mango seedlings of “Tommy” cultivar. The cuttings were irradiated with different doses of gamma radiation: 0 (control), 2.5, 5.0, 7.5 and 10.0 Gy, in a source of Cobalt-60 type Gammacell-220, installed in the Center for Nuclear Energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The correlation between the increase in plant height and the utilization of low levels of gamma irradiation may be attributed to its ability to induce cell division and enhance essential processes associated with nucleic acid synthesis (Arthur, 2021). In a previous investigation conducted by Kovacs and Keresztes (2022), it was observed that there was a drop in the average height of plants as the irradiation dose was raised.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The correlation between the increase in plant height and the utilization of low levels of gamma irradiation may be attributed to its ability to induce cell division and enhance essential processes associated with nucleic acid synthesis (Arthur, 2021). In a previous investigation conducted by Kovacs and Keresztes (2022), it was observed that there was a drop in the average height of plants as the irradiation dose was raised.…”
Section: Discussionmentioning
confidence: 97%
“…Gamma irradiation serves as a widely utilized physical mutagen and proves highly e cient in introducing genetic variations in several fruits, including Strawberry (El Oualkadi et al 2019), Guava (Singh S et al 2018), citrus (Pérez-Jiménez et al 2020), Mango (Arthur et al 2021), Grape (Surakshitha et al 2017), Papaya (Chaudhari et al 2022), Pear (Predieri et al 2000), and Kiwifruit (Yook et al 2009). Two factors in uence the impact of gamma rays on plant growth characters.…”
Section: Introductionmentioning
confidence: 99%
“…Induced mutation by Gamma ray irradiation to improve plant characters were reported in many plant species i.e. wheat (Di Pane et al, 2018;Dwinanda et al, 2020), rice (Abdelnour-Esquivel et al, 2020), mango (Arthur, 2021) and avocado (Elmageid & Al-Kfrawey, 2018). Testing of plant genetic diversity could be done using morphological markers such as leaf macro-morphology, by observing its phenotypic appearance (Herison et al, 2018;Tahir et al, 2019;Ihsan & Santoso, 2020).…”
Section: Introductionmentioning
confidence: 99%